LEKSIKON ALAT DAN AKTIVITAS BERTANAM PADI DALAM BAHASA JAWA - R Hery Budhiono (Kantor Bahasa Sulawesi Tenggara, 2017)
There are a great number of researches and writings deal with the Javanese language. Its scopes and domains have been such an attractive topics to be discussed globally. The Javanese language spoken in Pemalang is not an exception. However, some aspects of the language have not been disscussed yet, such as lexicon of tools and rice-farming activities. This research focuses on the lexicon of tools and rice-farming activities in Pemalang subdialect. The aim of the research is to inventory lexemes in such domain, describes their meanings, and identifies lexemes in common semantic fields. The writer uses recording and note-taking technique in collecting data. Based on the data, the writer identifies some lexemes of tools, such asblak, luku, garu, korokan, peret, pacul, andpancong; and lexemes of activities, such asnyebar, ngluku, nggaru, tandur, ngorok, derep, matun, gampung, nggejok, lajo, mbaron, pelanggaran, meret, and nggaleng. Based on the analysis, the writer finds that (1) the lexemes nggaru-ngluku,pacul-pancong as well as nggejog and meret share common semantic field and (2) some lexemes have officiallybeing part of the Indonesian lexicon, such as matun, derep, luku, and garu.